Hypotension and bradycardia before spinal anesthesia - Zapata,Carlos Javier Shiraishi (2017)
Abstract I report a case of hypotension and bradycardia before spinal anesthesia in a pregnant woman with mild to moderate hypertension treated with nifedipine and methyldopa, scheduled for an elective cesarean delivery. She had the history of neurally-mediated syncopes. Two main factors (increased vagal tone and adverse effects of antihypertensive drugs) could explain the hypotension and bradycardia before spinal anesthesia. Monitoring allowed recognizing the problem and corrected it. Thus, it was avoided a disaster in anesthesia, as hemodynamic changes after spinal anesthesia, they would have joined to previous hypotension and bradycardia, which would have caused even a cardiac arrest.